Negotiating classroom pedagogy for effective teaching - learning - Hashim, Che Noraini; Salleh, Mohamad Johdi (2011)
Effective teachers make the most important aspect of any educational program. The draw on a growing body of research knowledge about the nature of learning and on the art of teaching. The effective teacher can help overcome obstacles to the learning process, obstacles like poor materials, inadequate equipment, negative self-image (of the learner), and so on, while creating optimal conditions for learning. Unfortunately, many untrained or ineffective teachers are still teaching in classrooms using concepts of such as Strategy, Approach, Method, Technique and Activity interchangeably. This paper will look closely at each concept and discuss why they have become important issues in today’s education. The later part of this paper will also elaborate on only the three main concepts: strategies, approaches as well as classroom techniques. Finally, the paper lists the essential teaching skills which should not be overlooked by any teacher if effective teaching is to be his/her goal.